Pengaruh Sistem Informasi Manajemen Terhadap Kinerja Karyawan Pada PT. Primanusa Globalindo Pekanbaru - Jeli Nata Liyas, Ferisca Nur Widyanti (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
The purpose of this study was to determine the effect of management information systems on employee performance at PT. Primanusa Globalindo Pekanbaru. The sample of this study were employees who worked at PT. Primanusa Globalindo Pekanbaru. Data collection was carried out with questionnaires distributed directly to employees totaling 54 questionnaires. Statistical methods using Simple Linear Regression Analysis with hypothesis testing statistical tests t. From the overall response of respondents to the variable management information system at PT. Primanusa Globalindo Pekanbaru with an average score of 4.61 shows the response of respondents to the statement on the management information system variable is very agree. From the overall response of respondents to the variable employee performance at PT. Primanusa Globalindo Pekanbaru with an average score of 4.38 shows the response of respondents to statements on employee performance variables is agreed. T value of 4.048. While the critical value according to the table with a significant level of 5% using the formula t table (α / 2; n - k) k = 1 and n = 54 is 2.00575, because t arithmetic> t table then Hο is rejected. This means that the Management Information System has a positive effect on Employee Performance. With the meaning of the word Hypothesis (Ha) accepted. Positive t value indicates that the Management Information System variable has a direct relationship with Employee Performance at PT. Primanusa Globalindo Pekanbaru.